Revival Oscillations in a Closed Bromate‐1, 4‐Cyclohexanedione‐Acid System with Ferroin. Issue 12 (15th October 2021) - Kettunen, Petteri; Huh, Do Sung; Szalai, István; Yamaguchi, Tomohiko
Abstract: An unusual phenomenon of revival waves and oscillations is studied in a closed bromate‐1, 4‐cyclohexanedione reaction system containing ferroin catalyst. Experiments with varying initial 1, 4‐cyclohexanedione and bromate concentrations show that revival oscillations spontaneously emerge at a narrow area of the reaction conditions. Numerical calculations of a kinetic model consisting of 22 reactions and 15 species are employed to gain understanding of the underlying mechanism contributing to such an exotic dynamics. The simulations are able to reproduce the qualitative, but not yet quantitative properties of the experimentally observed revival oscillations. Abstract : Revival of oscillations in a closed chemical system is studied in laboratory experiments and by numerical calculations. The system is composed of bromate‐1, 4‐cyclohexanedione‐acid and ferroin catalyst, and its kinetic model consisted of 22 reactions and 15 species. This is the first report of successful simulation of this experimentally observed exotic phenomenon.